An auxin-mediated shift toward growth isotropy promotes organ formation at the shoot meristem in Arabidopsis - Sassi, Massimiliano; Ali, Olivier; Boudon, Frédéric; Cloarec, Gladys; Abad, Ursula; Cellier, Coralie; Chen, Xu; Gilles, Benjamin; Milani, Pascale; Friml, Jirí; Vernoux, Teva; Godin, Christophe; et al. (Current Biology)
To control morphogenesis, molecular regulatory networks have to interfere with the mechanical properties of the individual cells of developing organs and tissues, but how this is achieved is not well known. We study this issue here in the shoot meristem of higher plants, a group of undifferentiated cells where complex changes in growth rates and directions lead to the continuous formation of new organs [1, 2]. Here, we show that the plant hormone auxin plays an important role in this process via a dual, local effect on the extracellular matrix, the cell wall, which determines cell shape. Our study reveals that auxin not only causes a limited reduction in wall stiffness but also directly interferes with wall anisotropy via the regulation of cortical microtubule dynamics. We further show that to induce growth isotropy and organ outgrowth, auxin somehow interferes with the cortical microtubule-ordering activity of a network of proteins, including AUXIN BINDING PROTEIN 1 and KATANIN 1. Numerical simulations further indicate that the induced isotropy is sufficient to amplify the effects of the relatively minor changes in wall stiffness to promote organogenesis and the establishment of new growth axes in a robust manner.

Inhibition of cell expansion by rapid ABP1-mediated auxin effect on microtubules - Chen, Xu; Grandont, Laurie; Li, Hongjiang; Hauschild, Robert; Paque, Sébastien; Abuzeineh, Anas; Rakusova, Hana; Benková, Eva; Perrot Rechenmann, Catherine; Friml, Jirí (Nature)
The prominent and evolutionarily ancient role of the plant hormone auxin is the regulation of cell expansion. Cell expansion requires ordered arrangement of the cytoskeleton but molecular mechanisms underlying its regulation by signalling molecules including auxin are unknown. Here we show in the model plant Arabidopsis thaliana that in elongating cells exogenous application of auxin or redistribution of endogenous auxin induces very rapid microtubule re-orientation from transverse to longitudinal, coherent with the inhibition of cell expansion. This fast auxin effect requires auxin binding protein 1 (ABP1) and involves a contribution of downstream signalling components such as ROP6 GTPase, ROP-interactive protein RIC1 and the microtubule-severing protein katanin. These components are required for rapid auxin-and ABP1-mediated re-orientation of microtubules to regulate cell elongation in roots and dark-grown hypocotyls as well as asymmetric growth during gravitropic responses.

SAC phosphoinositide phosphatases at the tonoplast mediate vacuolar function in Arabidopsis - Nováková, Petra; Hirsch, Sibylle; Feraru, Elena; Tejos, Ricardo; Van Wijk, Ringo; Viaene, Tom; Heilmann, Mareike; Lerche, Jennifer; De Rycke, Riet; Feraru, Mugurel; Grones, Peter; Van Montagu, Marc; et al. (PNAS)
Phosphatidylinositol (PtdIns) is a structural phospholipid that can be phosphorylated into various lipid signaling molecules, designated polyphosphoinositides (PPIs). The reversible phosphorylation of PPIs on the 3, 4, or 5 position of inositol is performed by a set of organelle-specific kinases and phosphatases, and the characteristic head groups make these molecules ideal for regulating biological processes in time and space. In yeast and mammals, PtdIns3P and PtdIns(3,5)P2 play crucial roles in trafficking toward the lytic compartments, whereas the role in plants is not yet fully understood. Here we identified the role of a land plant-specific subgroup of PPI phosphatases, the suppressor of actin 2 (SAC2) to SAC5, during vacuolar trafficking and morphogenesis in Arabidopsis thaliana. SAC2-SAC5 localize to the tonoplast along with PtdIns3P, the presumable product of their activity. In SAC gain- and loss-of-function mutants, the levels of PtdIns monophosphates and bisphosphates were changed, with opposite effects on the morphology of storage and lytic vacuoles, and the trafficking toward the vacuoles was defective. Moreover, multiple sac knockout mutants had an increased number of smaller storage and lytic vacuoles, whereas extralarge vacuoles were observed in the overexpression lines, correlating with various growth and developmental defects. The fragmented vacuolar phenotype of sac mutants could be mimicked by treating wild-type seedlings with PtdIns(3,5)P2, corroborating that this PPI is important for vacuole morphology. Taken together, these results provide evidence that PPIs, together with their metabolic enzymes SAC2-SAC5, are crucial for vacuolar trafficking and for vacuolar morphology and function in plants.

Insights into the localization and function of the membrane trafficking regulator GNOM ARF-GEF at the Golgi apparatus in Arabidopsis - Naramoto, Satoshi; Otegui, Marisa; Kutsuna, Natsumaro; De Rycke, Riet; Dainobu, Tomoko; Karampelias, Michael; Fujimoto, Masaru; Feraru, Elena; Miki, Daisuke; Fukuda, Hiroo; Nakano, Akihiko; Friml, Jirí (Plant Cell)
GNOM is one of the most characterized membrane trafficking regulators in plants, with crucial roles in development. GNOM encodes an ARF-guanine nucleotide exchange factor (ARF-GEF) that activates small GTPases of the ARF (ADP ribosylation factor) class to mediate vesicle budding at endomembranes. The crucial role of GNOM in recycling of PIN auxin transporters and other proteins to the plasma membrane was identified in studies using the ARF-GEF inhibitor brefeldin A (BFA). GNOM, the most prominent regulator of recycling in plants, has been proposed to act and localize at so far elusive recycling endosomes. Here, we report the GNOM localization in context of its cellular function in Arabidopsis thaliana. State-of-the-art imaging, pharmacological interference, and ultrastructure analysis show that GNOM predominantly localizes to Golgi apparatus. Super-resolution confocal live imaging microscopy identified GNOM and its closest homolog GNOM-like 1 at distinct subdomains on Golgi cisternae. Short-term BFA treatment stabilizes GNOM at the Golgi apparatus, whereas prolonged exposures results in GNOM translocation to trans-Golgi network (TGN)/early endosomes (EEs). Malformed TGN/EE in gnom mutants suggests a role for GNOM in maintaining TGN/EE function. Our results redefine the subcellular action of GNOM and reevaluate the identity and function of recycling endosomes in plants.

WOX5-IAA17 feedback circuit-mediated cellular auxin response is crucial for the patterning of root stem cell niches in arabidopsis - Tian, Huiyu; Wabnik, Krzysztof T; Niu, Tiantian; Li, Hongjiang; Yu, Qianqian; Pollmann, Stephan; Vanneste, Steffen; Govaerts, Willy; Rolčík, Jakub; Geisler, Markus; Friml, Jirí; Ding, Zhaojun (Molecular Plant)
In plants, the patterning of stem cell-enriched meristems requires a graded auxin response maximum that emerges from the concerted action of polar auxin transport, auxin biosynthesis, auxin metabolism, and cellular auxin response machinery. However, mechanisms underlying this auxin response maximum-mediated root stem cell maintenance are not fully understood. Here, we present unexpected evidence that WUSCHEL-RELATED HOMEOBOX 5 (WOX5) transcription factor modulates expression of auxin biosynthetic genes in the quiescent center (QC) of the root and thus provides a robust mechanism for the maintenance of auxin response maximum in the root tip. This WOX5 action is balanced through the activity of indole-3-acetic acid 17 (IAA17) auxin response repressor. Our combined genetic, cell biology, and computational modeling studies revealed a previously uncharacterized feedback loop linking WOX5-mediated auxin production to IAA17-dependent repression of auxin responses. This WOX5-IAA17 feedback circuit further assures the maintenance of auxin response maximum in the root tip and thereby contributes to the maintenance of distal stem cell (DSC) populations. Our experimental studies and in silico computer simulations both demonstrate that the WOX5-IAA17 feedback circuit is essential for the maintenance of auxin gradient in the root tip and the auxin-mediated root DSC differentiation.

Cell surface ABP1-TMK auxin sensing complex activates ROP GTPase signaling - Xu, Tongda; Dai, Ning; Chen, Jisheng; Nagawa, Shingo; Cao, Min; Li, Hongjiang; Zhou, Zimin; Chen, Xu; De Rycke, Riet; Rakusová, Hana; Wang, Wen; Jones, Alan; et al. (Science)
Auxin-binding protein 1 (ABP1) was discovered nearly 40 years ago and was shown to be essential for plant development and morphogenesis, but its mode of action remains unclear. Here, we report that the plasma membrane-localized transmembrane kinase (TMK) receptor-like kinases interact with ABP1 and transduce auxin signal to activate plasma membrane-associated ROPs [Rho-like guanosine triphosphatases (GTPase) from plants], leading to changes in the cytoskeleton and the shape of leaf pavement cells in Arabidopsis. The interaction between ABP1 and TMK at the cell surface is induced by auxin and requires ABP1 sensing of auxin. These findings show that TMK proteins and ABP1 form a cell surface auxin perception complex that activates ROP signaling pathways, regulating nontranscriptional cytoplasmic responses and associated fundamental processes.

Rho-GTPase-regulated vesicle trafficking in plant cell polarity - Chen, Xu; Friml, Jirí (Biochemical Society Transactions)
ROPs (Rho of plants) belong to a large family of plant-specific Rho-like small GTPases that function as essential molecular switches to control diverse cellular processes including cytoskeleton organization, cell polarization, cytokinesis, cell differentiation and vesicle trafficking. Although the machineries of vesicle trafficking and cell polarity in plants have been individually well addressed, how ROPs co-ordinate those processes is still largely unclear. Recent progress has been made towards an understanding of the coordination of ROP signalling and trafficking of PIN (PINFORMED) transporters for the plant hormone auxin in both root and leaf pavement cells. PIN transporters constantly shuttle between the endosomal compartments and the polar plasma membrane domains, therefore the modulation of PIN-dependent auxin transport between cells is a main developmental output of ROP-regulated vesicle trafficking. The present review focuses on these cellular mechanisms, especially the integration of ROP-based vesicle trafficking and plant cell polarity.

Plant biology: Gatekeepers of the road to protein perdition - Sauer, Michael; Friml, Jirí (Current Biology)
Targeting membrane proteins for degradation requires the sequential action of ESCRT sub-complexes ESCRT-0 to ESCRT-III. Although this machinery is generally conserved among kingdoms, plants lack the essential ESCRT-0 components. A new report closes this gap by identifying a novel protein family that substitutes for ESCRT-0 function in plants.

Bipolar plasma membrane distribution of phosphoinositides and their requirement for auxin-mediated cell polarity and patterning in Arabidopsis - Tejos, Ricardo; Sauer, Michael; Vanneste, Steffen; Palacios-Gomez, MiriamPalacios; Li, Hongjiang; Heilmann, Mareike; Van Wijk, Ringo; Vermeer, Joop; Heilmann, Ingo; Munnik, Teun; Friml, Jirí (Plant Cell)
Cell polarity manifested by asymmetric distribution of cargoes, such as receptors and transporters, within the plasma membrane (PM) is crucial for essential functions in multicellular organisms. In plants, cell polarity (re)establishment is intimately linked to patterning processes. Despite the importance of cell polarity, its underlying mechanisms are still largely unknown, including the definition and distinctiveness of the polar domains within the PM. Here, we show in Arabidopsis thaliana that the signaling membrane components, the phosphoinositides phosphatidylinositol 4-phosphate (PtdIns4P) and phosphatidylinositol 4, 5-bisphosphate [PtdIns(4, 5)P2] as well as PtdIns4P 5-kinases mediating their interconversion, are specifically enriched at apical and basal polar plasma membrane domains. The PtdIns4P 5-kinases PIP5K1 and PIP5K2 are redundantly required for polar localization of specifically apical and basal cargoes, such as PIN-FORMED transporters for the plant hormone auxin. As a consequence of the polarity defects, instructive auxin gradients as well as embryonic and postembryonic patterning are severely compromised. Furthermore, auxin itself regulates PIP5K transcription and PtdIns4P and PtdIns(4, 5)P2 levels, in particular their association with polar PM domains. Our results provide insight into the polar domain-delineating mechanisms in plant cells that depend on apical and basal distribution of membrane lipids and are essential for embryonic and postembryonic patterning.

Auxin transport and activity regulate stomatal patterning and development - Le, Jie; Liu, Xuguang; Yang, Kezhen; Chen, Xiaolan; Zhu, Lingling; Wang, Hongzhe; Wang, Ming; Vanneste, Steffen; Morita, Miyo; Tasaka, Masao; Ding, Zhaojun; Friml, Jirí; et al. (Nature Communications)
Stomata are two-celled valves that control epidermal pores whose spacing optimizes shoot-atmosphere gas exchange. They develop from protodermal cells after unequal divisions followed by an equal division and differentiation. The concentration of the hormone auxin, a master plant developmental regulator, is tightly controlled in time and space, but its role, if any, in stomatal formation is obscure. Here dynamic changes of auxin activity during stomatal development are monitored using auxin input (DII-VENUS) and output (DR5:VENUS) markers by time-lapse imaging. A decrease in auxin levels in the smaller daughter cell after unequal division presages the acquisition of a guard mother cell fate whose equal division produces the two guard cells. Thus, stomatal patterning requires auxin pathway control of stem cell compartment size, as well as auxin depletion that triggers a developmental switch from unequal to equal division.

Cytokinin controls polarity of PIN1-dependent Auxin transport during lateral root organogenesis - Marhavy, Peter; Duclercq, Jérôme; Weller, Benjamin; Feraru, Elena; Bielach, Agnieszka; Offringa, Remko; Friml, Jirí; Schwechheimer, Claus; Murphy, Angus; Benková, Eva (Current Biology)
The plant hormones auxin and cytokinin mutually coordinate their activities to control various aspects of development [1-9], and their crosstalk occurs at multiple levels [10, 11]. Cytokinin-mediated modulation of auxin transport provides an efficient means to regulate auxin distribution in plant organs. Here, we demonstrate that cytokinin does not merely control the overall auxin flow capacity, but might also act as a polarizing cue and control the auxin stream directionality during plant organogenesis. Cytokinin enhances the PIN-FORMED1 (PIN1) auxin transporter depletion at specific polar domains, thus rearranging the cellular PIN polarities and directly regulating the auxin flow direction. This selective cytokinin sensitivity correlates with the PIN protein phosphorylation degree. PIN1 phosphomimicking mutations, as well as enhanced phosphorylation in plants with modulated activities of PIN-specific kinases and phosphatases, desensitize PIN1 to cytokinin. Our results reveal conceptually novel, cytokinin-driven polarization mechanism that operates in developmental processes involving rapid auxin stream redirection, such as lateral root organogenesis, in which a gradual PIN polarity switch defines the growth axis of the newly formed organ.

Bimodal regulation of ICR1 levels generates self-organizing auxin distribution - Hazak, Ora; Obolski, Uri; Prat, Tomas; Friml, Jiří; Hadany, Lilach; Yalovsky, Shaul (PNAS)
Auxin polar transport, local maxima, and gradients have become an importantmodel system for studying self-organization. Auxin distribution is regulated by auxin-dependent positive feedback loops that are not well-understood at the molecular level. Previously, we showed the involvement of the RHO of Plants (ROP) effector INTERACTOR of CONSTITUTIVELY active ROP 1 (ICR1) in regulation of auxin transport and that ICR1 levels are posttranscriptionally repressed at the site of maximum auxin accumulation at the root tip. Here, we show that bimodal regulation of ICR1 levels by auxin is essential for regulating formation of auxin local maxima and gradients. ICR1 levels increase concomitant with increase in auxin response in lateral root primordia, cotyledon tips, and provascular tissues. However, in the embryo hypophysis and root meristem, when auxin exceeds critical levels, ICR1 is rapidly destabilized by an SCF(TIR1/AFB) [SKP, Cullin, F-box (transport inhibitor response 1/auxin signaling F-box protein)]-dependent auxin signaling mechanism. Furthermore, ectopic expression of ICR1 in the embryo hypophysis resulted in reduction of auxin accumulation and concomitant root growth arrest. ICR1 disappeared during root regeneration and lateral root initiation concomitantly with the formation of a local auxin maximum in response to external auxin treatments and transiently after gravitropic stimulation. Destabilization of ICR1 was impaired after inhibition of auxin transport and signaling, proteasome function, and protein synthesis. A mathematical model based on these findings shows that an in vivo-like auxin distribution, rootward auxin flux, and shootward reflux can be simulated without assuming preexisting tissue polarity. Our experimental results and mathematical modeling indicate that regulation of auxin distribution is tightly associated with auxin-dependent ICR1 levels.

Directional auxin transport mechanisms in early diverging land plants - Viaene, Tom; Landberg, Katarina; Thelander, Mattias; Medvecka, Eva; Pederson, Eric; Feraru, Elena; Cooper, Endymion; Karimi, Mansour; Delwiche, Charles; Ljung, Karin; Geisler, Markus; Sundberg, Eva; et al. (Current Biology)
The emergence and radiation of multicellular land plants was driven by crucial innovations to their body plans [1]. The directional transport of the phytohormone auxin represents a key, plant-specific mechanism for polarization and patterning in complex seed plants [2-5]. Here, we show that already in the early diverging land plant lineage, as exemplified by the moss Physcomitrella patens, auxin transport by PIN transporters is operational and diversified into ER-localized and plasma membrane-localized PIN proteins. Gain-of-function and loss-of-function analyses revealed that PIN-dependent intercellular auxin transport in Physcomitrella mediates crucial developmental transitions in tip-growing filaments and waves of polarization and differentiation in leaf-like structures. Plasma membrane PIN proteins localize in a polar manner to the tips of moss filaments, revealing an unexpected relation between polarization mechanisms in moss tip-growing cells and multicellular tissues of seed plants. Our results trace the origins of polarization and auxin-mediated patterning mechanisms and highlight the crucial role of polarized auxin transport during the evolution of multicellular land plants.

Cellular events during interfascicular cambium ontogenesis in inflorescence stems of Arabidopsis - Mazur, Ewa; Kurczyñska, Ewa; Friml, Jiří (Protoplasma)
Development of cambium and its activity is important for our knowledge of the mechanism of secondary growth. Arabidopsis thaliana emerges as a good model plant for such a kind of study. Thus, this paper reports on cellular events taking place in the interfascicular regions of inflorescence stems of A. thaliana, leading to the development of interfascicular cambium from differentiated interfascicular parenchyma cells (IPC). These events are as follows: appearance of auxin accumulation, PIN1 gene expression, polar PIN1 protein localization in the basal plasma membrane and periclinal divisions. Distribution of auxin was observed to be higher in differentiating into cambium parenchyma cells compared to cells within the pith and cortex. Expression of PIN1 in IPC was always preceded by auxin accumulation. Basal localization of PIN1 was already established in the cells prior to their periclinal division. These cellular events initiated within parenchyma cells adjacent to the vascular bundles and successively extended from that point towards the middle region of the interfascicular area, located between neighboring vascular bundles. The final consequence of which was the closure of the cambial ring within the stem. Changes in the chemical composition of IPC walls were also detected and included changes of pectic epitopes, xyloglucans (XG) and extensins rich in hydroxyproline (HRGPs). In summary, results presented in this paper describe interfascicular cambium ontogenesis in terms of successive cellular events in the interfascicular regions of inflorescence stems of Arabidopsis.

Polar delivery in plants; commonalities and differences to animal epithelial cells - Kania, Urszula; Fendrych, Matyas; Friml, Jiřĺ (Open Biology)
Although plant and animal cells use a similar core mechanism to deliver proteins to the plasma membrane, their different lifestyle, body organization and specific cell structures resulted in the acquisition of regulatory mechanisms that vary in the two kingdoms. In particular, cell polarity regulators do not seem to be conserved, because genes encoding key components are absent in plant genomes. In plants, the broad knowledge on polarity derives from the study of auxin transporters, the PIN-FORMED proteins, in the model plant Arabidopsis thaliana. In animals, much information is provided from the study of polarity in epithelial cells that exhibit basolateral and luminal apical polarities, separated by tight junctions. In this review, we summarize the similarities and differences of the polarization mechanisms between plants and animals and survey the main genetic approaches that have been used to characterize new genes involved in polarity establishment in plants, including the frequently used forward and reverse genetics screens as well as a novel chemical genetics approach that is expected to overcome the limitation of classical genetics methods.

BEX1/ARF1A1C is required for BFA-sensitive recycling of PIN auxin transporters and auxin-mediated development in arabidopsis - Tanaka, Hirokazu; Nodzyński, Tomasz; Kitakura, Saeko; Feraru, Mugurel; Sasabe, Michiko; Ishikawa, Tomomi; Kleine Vehn, Jürgen; Kakimoto, Tatsuo; Friml, Jirí (Plant and Cell Physiology)
Correct positioning of membrane proteins is an essential process in eukaryotic organisms. The plant hormone auxin is distributed through intercellular transport and triggers various cellular responses. Auxin transporters of the PIN-FORMED (PIN) family localize asymmetrically at the plasma membrane (PM) and mediate the directional transport of auxin between cells. A fungal toxin, brefeldin A (BFA), inhibits a subset of guanine nucleotide exchange factors for ADP-ribosylation factor small GTPases (ARF GEFs) including GNOM, which plays a major role in localization of PIN1 predominantly to the basal side of the PM. The Arabidopsis genome encodes 19 ARF-related putative GTPases. However, ARF components involved in PIN1 localization have been genetically poorly defined. Using a fluorescence imaging-based forward genetic approach, we identified an Arabidopsis mutant, bfa-visualized exocytic trafficking defective1 (bex1), in which PM localization of PIN1-green fluorescent protein (GFP) as well as development is hypersensitive to BFA. We found that in bex1 a member of the ARF1 gene family, ARF1A1C, was mutated. ARF1A1C localizes to the trans-Golgi network/early endosome and Golgi apparatus, acts synergistically to BEN1/MIN7 ARF GEF and is important for PIN recycling to the PM. Consistent with the developmental importance of PIN proteins, functional interference with ARF1 resulted in an impaired auxin response gradient and various developmental defects including embryonic patterning defects and growth arrest. Our results show that ARF1A1C is essential for recycling of PIN auxin transporters and for various auxin-dependent developmental processes.

VAN4 encodes a putative TRS120 that is required for normal cell growth and vein development in arabidopsis - Naramoto, Satoshi; Nodzyński, Tomasz; Dainobu, Tomoko; Takatsuka, Hirotomo; Okada, Teruyo; Friml, Jirí; Fukuda, Hiroo (Plant and Cell Physiology)
Leaf venation develops complex patterns in angiosperms, but the mechanism underlying this process is largely unknown. To elucidate the molecular mechanisms governing vein pattern formation, we previously isolated vascular network defective (van) mutants that displayed venation discontinuities. Here, we report the phenotypic analysis of van4 mutants, and we identify and characterize the VAN4 gene. Detailed phenotypic analysis shows that van4 mutants are defective in procambium cell differentiation and subsequent vascular cell differentiation. Reduced shoot and root cell growth is observed in van4 mutants, suggesting that VAN4 function is important for cell growth and the establishment of venation continuity. Consistent with these phenotypes, the VAN4 gene is strongly expressed in vascular and meristematic cells. VAN4 encodes a putative TRS120, which is a known guanine nucleotide exchange factor (GEF) for Rab GTPase involved in regulating vesicle transport, and a known tethering factor that determines the specificity of membrane fusion. VAN4 protein localizes at the trans-Golgi network/early endosome (TGN/EE). Aberrant recycling of the auxin efflux carrier PIN proteins is observed in van4 mutants. These results suggest that VAN4-mediated exocytosis at the TGN plays important roles in plant vascular development and cell growth in shoot and root. Our identification of VAN4 as a putative TRS120 shows that Rab GTPases are crucial (in addition to ARF GTPases) for continuous vascular development, and provides further evidence for the importance of vesicle transport in leaf vascular formation.

Allopolyploid origin of the Balkan endemic Ranunculus wettsteinii (Ranunculaceae) inferred from nuclear and plastid DNA sequences - Cires Rodriguez, Eduardo; Baltisberger, Matthias; Cuesta, Candela; Vargas, Pablo; Prieto, José (Organisms Diversity and Evolution)
The Balkan Peninsula, characterized by high rates of endemism, is recognised as one of the most diverse and species-rich areas of Europe. However, little is known about the origin of Balkan endemics. The present study addresses the phylogenetic position of the Balkan endemic Ranunculus wettsteinii, as well as its taxonomic status and relationship with the widespread R. parnassiifolius, based on nuclear DNA (internal transcribed spacer, ITS) and plastid regions (rpl32-trnL, rps16-trnQ, trnK-matK and ycf6-psbM). Maximum parsimony and Bayesian inference analyses revealed a well-supported clade formed by accessions of R. wettsteinii. Furthermore, our phylogenetic and network analyses supported previous hypotheses of a likely allopolyploid origin for R. wettsteinii between R. montenegrinus and R. parnassiifolius, with the latter as the maternal parent.

The TPLATE adaptor complex drives clathrin-mediated endocytosis in plants - Gadeyne, Astrid; Sánchez Rodríguez, Clara; Vanneste, Steffen; Di Rubbo, Simone; Zauber, Henrik; Vanneste, Kevin; Van Leene, Jelle; De Winne, Nancy; Eeckhout, Dominique; Persiau, Geert; Van De Slijke, Eveline; Cannoot, Bernard; et al. (Cell)
Clathrin-mediated endocytosis is the major mechanism for eukaryotic plasma membrane-based proteome turn-over. In plants, clathrin-mediated endocytosis is essential for physiology and development, but the identification and organization of the machinery operating this process remains largely obscure. Here, we identified an eight-core-component protein complex, the TPLATE complex, essential for plant growth via its role as major adaptor module for clathrin-mediated endocytosis. This complex consists of evolutionarily unique proteins that associate closely with core endocytic elements. The TPLATE complex is recruited as dynamic foci at the plasma membrane preceding recruitment of adaptor protein complex 2, clathrin, and dynamin-related proteins. Reduced function of different complex components severely impaired internalization of assorted endocytic cargoes, demonstrating its pivotal role in clathrin-mediated endocytosis. Taken together, the TPLATE complex is an early endocytic module representing a unique evolutionary plant adaptation of the canonical eukaryotic pathway for clathrin-mediated endocytosis.

Analyzing the in vivo status of exogenously applied auxins: A HPLC-based method to characterize the intracellularly localized auxin transporters - Simon, Sibu; Skůpa, Petr; Dobrev, Petre; Petrášek, Jan; Zažímalová, Eva; Friml, Jirí (Plant Chemical Genomics)
Exogenous application of biologically important molecules for plant growth promotion and/or regulation is very common both in plant research and horticulture. Plant hormones such as auxins and cytokinins are classes of compounds which are often applied exogenously. Nevertheless, plants possess a well-established machinery to regulate the active pool of exogenously applied compounds by converting them to metabolites and conjugates. Consequently, it is often very useful to know the in vivo status of applied compounds to connect them with some of the regulatory events in plant developmental processes. The in vivo status of applied compounds can be measured by incubating plants with radiolabeled compounds, followed by extraction, purification, and HPLC metabolic profiling of plant extracts. Recently we have used this method to characterize the intracellularly localized PIN protein, PIN5. Here we explain the method in detail, with a focus on general application.

Expression of TWISTED DWARF1 lacking its in-plane membrane anchor leads to increased cell elongation and hypermorphic growth - Bailly, Aurélien; Wang, Bangjun; Zwiewka, Marta; Pollmann, Stephan; Schenck, Daniel; Lüthen, Hartwig; Schulz, Alexander; Friml, Jirí; Geisler, Markus (Plant Journal)
Plant growth is achieved predominantly by cellular elongation, which is thought to be controlled on several levels by apoplastic auxin. Auxin export into the apoplast is achieved by plasma membrane efflux catalysts of the PIN-FORMED (PIN) and ATP-binding cassette protein subfamily B/phosphor- glycoprotein (ABCB/PGP) classes; the latter were shown to depend on interaction with the FKBP42, TWISTED DWARF1 (TWD1). Here by using a transgenic approach in combination with phenotypical, biochemical and cell biological analyses we demonstrate the importance of a putative C-terminal in-plane membrane anchor of TWD1 in the regulation of ABCB-mediated auxin transport. In contrast with dwarfed twd1 loss-of-function alleles, TWD1 gain-of-function lines that lack a putative in-plane membrane anchor (HA-TWD1-Ct) show hypermorphic plant architecture, characterized by enhanced stem length and leaf surface but reduced shoot branching. Greater hypocotyl length is the result of enhanced cell elongation that correlates with reduced polar auxin transport capacity for HA-TWD1-Ct. As a consequence, HA-TWD1-Ct displays higher hypocotyl auxin accumulation, which is shown to result in elevated auxin-induced cell elongation rates. Our data highlight the importance of C-terminal membrane anchoring for TWD1 action, which is required for specific regulation of ABCB-mediated auxin transport. These data support a model in which TWD1 controls lateral ABCB1-mediated export into the apoplast, which is required for auxin-mediated cell elongation.

Inter-regulation of the unfolded protein response and auxin signaling - Chen, Yani; Aung, Kyaw; Rolčík, Jakub; Walicki, Kathryn; Friml, Jirí; Brandizzí, Federica (Plant Journal)
The unfolded protein response (UPR) is a signaling network triggered by overload of protein-folding demand in the endoplasmic reticulum (ER), a condition termed ER stress. The UPR is critical for growth and development; nonetheless, connections between the UPR and other cellular regulatory processes remain largely unknown. Here, we identify a link between the UPR and the phytohormone auxin, a master regulator of plant physiology. We show that ER stress triggers down-regulation of auxin receptors and transporters in Arabidopsis thaliana. We also demonstrate that an Arabidopsis mutant of a conserved ER stress sensor IRE1 exhibits defects in the auxin response and levels. These data not only support that the plant IRE1 is required for auxin homeostasis, they also reveal a species-specific feature of IRE1 in multicellular eukaryotes. Furthermore, by establishing that UPR activation is reduced in mutants of ER-localized auxin transporters, including PIN5, we define a long-neglected biological significance of ER-based auxin regulation. We further examine the functional relationship of IRE1 and PIN5 by showing that an ire1 pin5 triple mutant enhances defects of UPR activation and auxin homeostasis in ire1 or pin5. Our results imply that the plant UPR has evolved a hormone-dependent strategy for coordinating ER function with physiological processes.

Molecular mechanisms of patterning and subcellular trafficking in Arabidopsis thaliana - Marhavá, Petra
Phosphatidylinositol (Ptdlns) is a structural phospholipid that can be phosphorylated into various lipid signaling molecules, designated polyphosphoinositides (PPIs). The reversible phosphorylation of PPIs on the 3, 4, or 5 position of inositol is performed by a set of organelle-specific kinases and phosphatases, and the characteristic head groups make these molecules ideal for regulating biological processes in time and space. In yeast and mammals, Ptdlns3P and Ptdlns(3,5)P2 play crucial roles in trafficking toward the lytic compartments, whereas the role in plants is not yet fully understood. Here we identified the role of a land plant-specific subgroup of PPI phosphatases, the suppressor of actin 2 (SAC2) to SAC5, during vauolar trafficking and morphogenesis in Arabidopsis thaliana. SAC2-SAC5 localize to the tonoplast along with Ptdlns3P, the presumable product of their activity. in SAC gain- and loss-of-function mutants, the levels of Ptdlns monophosphates and bisphosphates were changed, with opposite effects on the morphology of storage and lytic vacuoles, and the trafficking toward the vacuoles was defective. Moreover, multiple sac knockout mutants had an increased number of smaller storage and lytic vacuoles, whereas extralarge vacuoles were observed in the overexpression lines, correlating with various growth and developmental defects. The fragmented vacuolar phenotype of sac mutants could be mimicked by treating wild-type seedlings with Ptdlns(3,5)P2, corroborating that this PPI is important for vacuole morphology. Taken together, these results provide evidence that PPIs, together with their metabolic enzymes SAC2-SAC5, are crucial for vacuolar trafficking and for vacuolar morphology and function in plants.

Calcium: The missing link in auxin action - Vanneste, Steffen; Friml, Jiří (Plants)
Due to their sessile lifestyles, plants need to deal with the limitations and stresses imposed by the changing environment. Plants cope with these by a remarkable developmental flexibility, which is embedded in their strategy to survive. Plants can adjust their size, shape and number of organs, bend according to gravity and light, and regenerate tissues that were damaged, utilizing a coordinating, intercellular signal, the plant hormone, auxin. Another versatile signal is the cation, Ca2+, which is a crucial second messenger for many rapid cellular processes during responses to a wide range of endogenous and environmental signals, such as hormones, light, drought stress and others. Auxin is a good candidate for one of these Ca2+-activating signals. However, the role of auxin-induced Ca2+ signaling is poorly understood. Here, we will provide an overview of possible developmental and physiological roles, as well as mechanisms underlying the interconnection of Ca2+ and auxin signaling.
Keywords: Plant Science; Ecology; Ecology; Evolution; Behavior and Systematics

ECHIDNA mediated post Golgi trafficking of auxin carriers for differential cell elongation - Boutté, Yohann; Jonsson, Kristoffer; Mcfarlane, Heather; Johnson, Errin; Gendre, Delphine; Swarup, Ranjan; Friml, Jirí; Samuels, Lacey; Robert, Stéphanie; Bhalerao, Rishikesh (PNAS)
The plant hormone indole-acetic acid (auxin) is essential for many aspects of plant development. Auxin-mediated growth regulation typically involves the establishment of an auxin concentration gradient mediated by polarly localized auxin transporters. The localization of auxin carriers and their amount at the plasma membrane are controlled by membrane trafficking processes such as secretion, endocytosis, and recycling. In contrast to endocytosis or recycling, how the secretory pathway mediates the localization of auxin carriers is not well understood. In this study we have used the differential cell elongation process during apical hook development to elucidate the mechanisms underlying the post-Golgi trafficking of auxin carriers in Arabidopsis. We show that differential cell elongation during apical hook development is defective in Arabidopsis mutant echidna (ech). ECH protein is required for the trans-Golgi network (TGN)-mediated trafficking of the auxin influx carrier AUX1 to the plasma membrane. In contrast, ech mutation only marginally perturbs the trafficking of the highly related auxin influx carrier LIKE-AUX1-3 or the auxin efflux carrier PIN-FORMED-3, both also involved in hook development. Electron tomography reveals that the trafficking defects in ech mutant are associated with the perturbation of secretory vesicle genesis from the TGN. Our results identify differential mechanisms for the post-Golgi trafficking of de novo-synthesized auxin carriers to plasma membrane from the TGN and reveal how trafficking of auxin influx carriers mediates the control of differential cell elongation in apical hook development.

Defining the selectivity of processes along the auxin response chain: A study using auxin analogues - Simon, Sibu; Kubeš, Martin; Baster, Pawel; Robert, Stéphanie; Dobrev, Petre; Friml, Jirí; Petrášek, Jan; Zažímalová, Eva (New Phytologist)
The mode of action of auxin is based on its non-uniform distribution within tissues and organs. Despite the wide use of several auxin analogues in research and agriculture, little is known about the specificity of different auxin-related transport and signalling processes towards these compounds. Using seedlings of Arabidopsis thaliana and suspension-cultured cells of Nicotiana tabacum (BY-2), the physiological activity of several auxin analogues was investigated, together with their capacity to induce auxin-dependent gene expression, to inhibit endocytosis and to be transported across the plasma membrane. This study shows that the specificity criteria for different auxin-related processes vary widely. Notably, the special behaviour of some synthetic auxin analogues suggests that they might be useful tools in investigations of the molecular mechanism of auxin action. Thus, due to their differential stimulatory effects on DR5 expression, indole-3-propionic (IPA) and 2,4,5-trichlorophenoxy acetic (2,4,5-T) acids can serve in studies of TRANSPORT INHIBITOR RESPONSE 1/AUXIN SIGNALLING F-BOX (TIR1/AFB)-mediated auxin signalling, and 5-fluoroindole-3-acetic acid (5-F-IAA) can help to discriminate between transcriptional and non-transcriptional pathways of auxin signalling. The results demonstrate that the major determinants for the auxin-like physiological potential of a particular compound are very complex and involve its chemical and metabolic stability, its ability to distribute in tissues in a polar manner and its activity towards auxin signalling machinery.

Retromer subunits VPS35A and VPS29 mediate prevacuolar compartment (PVC) function in Arabidopsis - Nodzyński, Tomasz; Feraru, Murguel; Hirsch, Sibylle; De Rycke, Riet; Nicuales, Claudiu; Van Leene, Jelle; De Jaeger, Geert; Vanneste, Steffen; Friml, Jirí (Molecular Plant)
Intracellular protein routing is mediated by vesicular transport which is tightly regulated in eukaryotes. The protein and lipid homeostasis depends on coordinated delivery of de novo synthesized or recycled cargoes to the plasma membrane by exocytosis and their subsequent removal by rerouting them for recycling or degradation. Here, we report the characterization of protein affected trafficking 3 (pat3) mutant that we identified by an epifluorescence-based forward genetic screen for mutants defective in subcellular distribution of Arabidopsis auxin transporter PIN1–GFP. While pat3 displays largely normal plant morphology and development in nutrient-rich conditions, it shows strong ectopic intracellular accumulations of different plasma membrane cargoes in structures that resemble prevacuolar compartments (PVC) with an aberrant morphology. Genetic mapping revealed that pat3 is defective in vacuolar protein sorting 35A (VPS35A), a putative subunit of the retromer complex that mediates retrograde trafficking between the PVC and trans-Golgi network. Similarly, a mutant defective in another retromer subunit, vps29, shows comparable subcellular defects in PVC morphology and protein accumulation. Thus, our data provide evidence that the retromer components VPS35A and VPS29 are essential for normal PVC morphology and normal trafficking of plasma membrane proteins in plants. In addition, we show that, out of the three VPS35 retromer subunits present in Arabidopsis thaliana genome, the VPS35 homolog A plays a prevailing role in trafficking to the lytic vacuole, presenting another level of complexity in the retromer-dependent vacuolar sorting.

Role of the Arabidopsis PIN6 auxin transporter in auxin homeostasis and auxin-mediated development - Cazzonelli, Christopher; Vanstraelen, Marleen; Simon, Sibu; Yin, Kuide; Carron Arthur, Ashley; Nisar, Nazia; Tarle, Gauri; Cuttriss, Abby; Searle, Iain; Benková, Eva; Mathesius, Ulrike; Masle, Josette; et al. (PLoS One)
Plant-specific PIN-formed (PIN) efflux transporters for the plant hormone auxin are required for tissue-specific directional auxin transport and cellular auxin homeostasis. The Arabidopsis PIN protein family has been shown to play important roles in developmental processes such as embryogenesis, organogenesis, vascular tissue differentiation, root meristem patterning and tropic growth. Here we analyzed roles of the less characterised Arabidopsis PIN6 auxin transporter. PIN6 is auxin-inducible and is expressed during multiple auxin-regulated developmental processes. Loss of pin6 function interfered with primary root growth and lateral root development. Misexpression of PIN6 affected auxin transport and interfered with auxin homeostasis in other growth processes such as shoot apical dominance, lateral root primordia development, adventitious root formation, root hair outgrowth and root waving. These changes in auxin-regulated growth correlated with a reduction in total auxin transport as well as with an altered activity of DR5-GUS auxin response reporter. Overall, the data indicate that PIN6 regulates auxin homeostasis during plant development.

Overexpression of the auxin binding PROTEIN1 modulates PIN-dependent auxin transport in tobacco cells - Čovanová, Milada; Sauer, Michael; Rychtář, Jan; Friml, Jirí; Petrášek, Jan; Zažímalová, Eva (PLoS One)
Background:Auxin binding protein 1 (ABP1) is a putative auxin receptor and its function is indispensable for plant growth and development. ABP1 has been shown to be involved in auxin-dependent regulation of cell division and expansion, in plasma-membrane-related processes such as changes in transmembrane potential, and in the regulation of clathrin-dependent endocytosis. However, the ABP1-regulated downstream pathway remains elusive.Methodology/Principal Findings:Using auxin transport assays and quantitative analysis of cellular morphology we show that ABP1 regulates auxin efflux from tobacco BY-2 cells. The overexpression of ABP1can counterbalance increased auxin efflux and auxin starvation phenotypes caused by the overexpression of PIN auxin efflux carrier. Relevant mechanism involves the ABP1-controlled vesicle trafficking processes, including positive regulation of endocytosis of PIN auxin efflux carriers, as indicated by fluorescence recovery after photobleaching (FRAP) and pharmacological manipulations.Conclusions/Significance:The findings indicate the involvement of ABP1 in control of rate of auxin transport across plasma membrane emphasizing the role of ABP1 in regulation of PIN activity at the plasma membrane, and highlighting the relevance of ABP1 for the formation of developmentally important, PIN-dependent auxin gradients.

The moss physcomitrella patens reproductive organ development is highly organized, affected by the two SHI/STY genes and by the level of active auxin in the SHI/STY expression domain - Landberg, Katarina; Pederson, Eric; Viaene, Tom; Bozorg, Behruz; Friml, Jirí; Jönsson, Henrik; Thelander, Mattias; Sundberg, Eva (Plant Physiology)
In order to establish a reference for analysis of the function of auxin and the auxin biosynthesis regulators SHORT INTERNODE/ STYLISH (SHI/STY) during Physcomitrella patens reproductive development, we have described male (antheridial) and female (archegonial) development in detail, including temporal and positional information of organ initiation. This has allowed us to define discrete stages of organ morphogenesis and to show that reproductive organ development in P. patens is highly organized and that organ phyllotaxis differs between vegetative and reproductive development. Using the PpSHI1 and PpSHI2 reporter and knockout lines, the auxin reporters GmGH3pro:GUS and PpPINApro:GFP-GUS, and the auxin-conjugating transgene PpSHI2pro:IAAL, we could show that the PpSHI genes, and by inference also auxin, play important roles for reproductive organ development in moss. The PpSHI genes are required for the apical opening of the reproductive organs, the final differentiation of the egg cell, and the progression of canal cells into a cell death program. The apical cells of the archegonium, the canal cells, and the egg cell are also sites of auxin responsiveness and are affected by reduced levels of active auxin, suggesting that auxin mediates PpSHI function in the reproductive organs.

A major facilitator superfamily transporter plays a dual role in polar auxin transport and drought stress tolerance in Arabidopsis - Remy, Estelle; Cabrito, Tânia; Baster, Pawel; Batista, Rita; Teixeira, Miguel; Friml, Jirí; Sá Correia, Isabel; Duque, Paula (Plant Cell)
Many key aspects of plant development are regulated by the polarized transport of the phytohormone auxin. Cellular auxin efflux, the rate-limiting step in this process, has been shown to rely on the coordinated action of PIN-formed (PIN) and B-type ATP binding cassette (ABCB) carriers. Here, we report that polar auxin transport in the Arabidopsis thaliana root also requires the action of a Major Facilitator Superfamily (MFS) transporter, Zinc-Induced Facilitator-Like 1 (ZIFL1). Sequencing, promoter-reporter, and fluorescent protein fusion experiments indicate that the full-length ZIFL1.1 protein and a truncated splice isoform, ZIFL1.3, localize to the tonoplast of root cells and the plasma membrane of leaf stomatal guard cells, respectively. Using reverse genetics, we show that the ZIFL1.1 transporter regulates various root auxin-related processes, while the ZIFL1.3 isoform mediates drought tolerance by regulating stomatal closure. Auxin transport and immunolocalization assays demonstrate that ZIFL1.1 indirectly modulates cellular auxin efflux during shootward auxin transport at the root tip, likely by regulating plasma membrane PIN2 abundance. Finally, heterologous expression in yeast revealed that ZIFL1.1 and ZIFL1.3 share H+-coupled K+ transport activity. Thus, by determining the subcellular and tissue distribution of two isoforms, alternative splicing dictates a dual function for the ZIFL1 transporter. We propose that this MFS carrier regulates stomatal movements and polar auxin transport by modulating potassium and proton fluxes in Arabidopsis cells.

Salicylic acid interferes with clathrin-mediated endocytic protein trafficking - Du, Yunlong; Tejos, Ricardo; Beck, Martina; Himschoot, Ellie; Li, Hongjiang; Robatzek, Silke; Vanneste, Steffen; Friml, Jirí (PNAS)
Removal of cargos from the cell surface via endocytosis is an efficient mechanism to regulate activities of plasma membrane (PM)-resident proteins, such as receptors or transporters. Salicylic acid (SA) is an important plant hormone that is traditionally associated with pathogen defense. Here, we describe an unanticipated effect of SA on subcellular endocytic cycling of proteins. Both exogenous treatments and endogenously enhanced SA levels repressed endocytosis of different PM proteins. The SA effect on endocytosis did not involve transcription or known components of the SA signaling pathway for transcriptional regulation. SA likely targets an endocytic mechanism that involves the coat protein clathrin, because SA interfered with the clathrin incidence at the PM and clathrin-deficient mutants were less sensitive to the impact of SA on the auxin distribution and root bending during the gravitropic response. By contrast, SA did not affect the ligand-induced endocytosis of the FLAGELLIN SENSING2 (FLS2) receptor during pathogen responses. Our data suggest that the established SA impact on transcription in plant immunity and the nontranscriptional effect of SA on clathrin-mediated endocytosis are independent mechanisms by which SA regulates distinct aspects of plant physiology.

Cell polarity and patterning by PIN trafficking through early endosomal compartments in arabidopsis thaliana - Tanaka, Hirokazu; Kitakura, Saeko; Rakusová, Hana; Uemura, Tomohiro; Feraru, Mugurel; De Rycke, Riet; Robert, Stéphanie; Kakimoto, Tatsuo; Friml, Jirí (PLoS Genetics)
PIN-FORMED (PIN) proteins localize asymmetrically at the plasma membrane and mediate intercellular polar transport of the plant hormone auxin that is crucial for a multitude of developmental processes in plants. PIN localization is under extensive control by environmental or developmental cues, but mechanisms regulating PIN localization are not fully understood. Here we show that early endosomal components ARF GEF BEN1 and newly identified Sec1/Munc18 family protein BEN2 are involved in distinct steps of early endosomal trafficking. BEN1 and BEN2 are collectively required for polar PIN localization, for their dynamic repolarization, and consequently for auxin activity gradient formation and auxin-related developmental processes including embryonic patterning, organogenesis, and vasculature venation patterning. These results show that early endosomal trafficking is crucial for cell polarity and auxin-dependent regulation of plant architecture.

Root ultraviolet b-sensitive1/weak auxin response3 is essential for polar auxin transport in arabidopsis - Yu, Hong; Karampelias, Michael; Robert, Stéphanie; Peer, Wendy; Swarup, Ranjan; Ye, Songqing; Ge, Lei; Cohen, Jerry; Murphy, Angus; Friml, Jirí; Estelle, Mark (Plant Physiology)
The phytohormone auxin regulates virtually every aspect of plant development. To identify new genes involved in auxin activity, a genetic screen was performed for Arabidopsis (Arabidopsis thaliana) mutants with altered expression of the auxin-responsive reporter DR5rev:GFP. One of the mutants recovered in the screen, designated as weak auxin response3 (wxr3), exhibits much lower DR5rev:GFP expression when treated with the synthetic auxin 2,4-dichlorophenoxyacetic acid and displays severe defects in root development. The wxr3 mutant decreases polar auxin transport and results in a disruption of the asymmetric auxin distribution. The levels of the auxin transporters AUXIN1 and PIN-FORMED are dramatically reduced in the wxr3 root tip. Molecular analyses demonstrate that WXR3 is ROOT ULTRAVIOLET B-SENSITIVE1 (RUS1), a member of the conserved Domain of Unknown Function647 protein family found in diverse eukaryotic organisms. Our data suggest that RUS1/WXR3 plays an essential role in the regulation of polar auxin transport by maintaining the proper level of auxin transporters on the plasma membrane.

An auxin transport mechanism restricts positive orthogravitropism in lateral roots - Rosquete, Michel; Von Wangenheim, Daniel; Marhavy, Peter; Barbez, Elke; Stelzer, Ernst; Benková, Eva; Maizel, Alexis; Kleine Vehn, Jürgen (Current Biology)
As soon as a seed germinates, plant growth relates to gravity to ensure that the root penetrates the soil and the shoot expands aerially. Whereas mechanisms of positive and negative orthogravitropism of primary roots and shoots are relatively well understood [1-3], lateral organs often show more complex growth behavior [4]. Lateral roots (LRs) seemingly suppress positive gravitropic growth and show a defined gravitropic set-point angle (GSA) that allows radial expansion of the root system (plagiotropism) [3, 4]. Despite its eminent importance for root architecture, it so far remains completely unknown how lateral organs partially suppress positive orthogravitropism. Here we show that the phytohormone auxin steers GSA formation and limits positive orthogravitropism in LR. Low and high auxin levels/signaling lead to radial or axial root systems, respectively. At a cellular level, it is the auxin transport-dependent regulation of asymmetric growth in the elongation zone that determines GSA. Our data suggest that strong repression of PIN4/PIN7 and transient PIN3 expression limit auxin redistribution in young LR columella cells. We conclude that PIN activity, by temporally limiting the asymmetric auxin fluxes in the tip of LRs, induces transient, differential growth responses in the elongation zone and, consequently, controls root architecture.

Arabidopsis TWISTED DWARF1 functionally interacts with auxin exporter ABCB1 on the root plasma membrane - Wang, Bangjun; Bailly, Aurélien; Zwiewk, Marta; Henrichs, Sina; Azzarello, Elisa; Mancuso, Stefano; Maeshima, Masayoshi; Friml, Jirí; Schulz, Alexander; Geisler, Markus (Plant Cell)
Plant architecture is influenced by the polar, cell-to-cell transport of auxin that is primarily provided and regulated by plasma membrane efflux catalysts of the PIN-FORMED and B family of ABC transporter (ABCB) classes. The latter were shown to require the functionality of the FK506 binding protein42 TWISTED DWARF1 (TWD1), although underlying mechanisms are unclear. By genetic manipulation of TWD1 expression, we show here that TWD1 affects shootward root auxin reflux and, thus, downstream developmental traits, such as epidermal twisting and gravitropism of the root. Using immunological assays, we demonstrate a predominant lateral, mainly outward-facing, plasma membrane location for TWD1 in the root epidermis characterized by the lateral marker ABC transporter G36/PLEIOTROPIC DRUG-RESISTANCE8/PENETRATION3. At these epidermal plasma membrane domains, TWD1 colocalizes with nonpolar ABCB1. In planta bioluminescence resonance energy transfer analysis was used to verify specific ABC transporter B1 (ABCB1)-TWD1 interaction. Our data support a model in which TWD1 promotes lateral ABCB-mediated auxin efflux via protein-protein interaction at the plasma membrane, minimizing reflux from the root apoplast into the cytoplasm.

Asymmetric gibberellin signaling regulates vacuolar trafficking of PIN auxin transporters during root gravitropism - Löfke, Christian; Zwiewka, Marta; Heilmann, Ingo; Van Montagu, Marc; Teichmann, Thomas; Friml, Jirí (PNAS)
Gravitropic bending of plant organs is mediated by an asymmetric signaling of the plant hormone auxin between the upper and lower side of the respective organ. Here, we show that also another plant hormone, gibberellic acid (GA), shows asymmetric action during gravitropic responses. Immunodetection using an antibody against GA and monitoring GA signaling output by downstream degradation of DELLA proteins revealed an asymmetric GA distribution and response with the maximum at the lower side of gravistimulated roots. Genetic or pharmacological manipulation of GA levels or response affects gravity-mediated auxin redistribution and root bending response. The higher GA levels at the lower side of the root correlate with increased amounts of PIN-FORMED2 (PIN2) auxin transporter at the plasma membrane. The observed increase in PIN2 stability is caused by a specific GA effect on trafficking of PIN proteins to lytic vacuoles that presumably occurs downstream of brefeldin A-sensitive endosomes. Our results suggest that asymmetric auxin distribution instructive for gravity-induced differential growth is consolidated by the asymmetric action of GA that stabilizes the PIN-dependent auxin stream along the lower side of gravistimulated roots.

SCF^TIR1 AFB-auxin signalling regulates PIN vacuolar trafficking and auxin fluxes during root gravitropism - Baster, Pawel; Robert, Stéphanie; Kleine Vehn, Jürgen; Vanneste, Steffen; Kania, Urszula; Grunewald, Wim; De Rybel, Bert; Beeckman, Tom; Friml, Jirí (EMBO Journal)
The distribution of the phytohormone auxin regulates many aspects of plant development including growth response to gravity. Gravitropic root curvature involves coordinated and asymmetric cell elongation between the lower and upper side of the root, mediated by differential cellular auxin levels. The asymmetry in the auxin distribution is established and maintained by a spatio-temporal regulation of the PIN-FORMED (PIN) auxin transporter activity. We provide novel insights into the complex regulation of PIN abundance and activity during root gravitropism. We show that PIN2 turnover is differentially regulated on the upper and lower side of gravistimulated roots by distinct but partially overlapping auxin feedback mechanisms. In addition to regulating transcription and clathrin-mediated internalization, auxin also controls PIN abundance at the plasma membrane by promoting their vacuolar targeting and degradation. This effect of elevated auxin levels requires the activity of SKP-Cullin-F-box TIR1/AFB (SCF TIR1/AFB)-dependent pathway. Importantly, also suboptimal auxin levels mediate PIN degradation utilizing the same signalling pathway. These feedback mechanisms are functionally important during gravitropic response and ensure fine-tuning of auxin fluxes for maintaining as well as terminating asymmetric growth.

The clathrin adaptor complex AP-2 mediates endocytosis of brassinosteroid INSENSITIVE1 in arabidopsis - Di Rubbo, Simone; Irani, Niloufer; Kim, Soo; Xu, Zheng; Gadeyne, Astrid; Dejonghe, Wim; Vanhoutte, Isabelle; Persiau, Geert; Eeckhout, Dominique; Simon, Sibu; Song, Kyungyoung; Kleine Vehn, Jürgen; et al. (Plant Cell)
Clathrin-mediated endocytosis (CME) regulates many aspects of plant development, including hormone signaling and responses to environmental stresses. Despite the importance of this process, the machinery that regulates CME in plants is largely unknown. In mammals, the heterotetrameric ADAPTOR PROTEIN COMPLEX-2 (AP-2) is required for the formation of clathrin-coated vesicles at the plasma membrane (PM). Although the existence of AP-2 has been predicted in Arabidopsis thaliana, the biochemistry and functionality of the complex is still uncharacterized. Here, we identified all the subunits of the Arabidopsis AP-2 by tandem affinity purification and found that one of the large AP-2 subunits, AP2A1, localized at the PM and interacted with clathrin. Furthermore, endocytosis of the leucine-rich repeat receptor kinase, BRASSINOSTEROID INSENSITIVE1 (BRI1), was shown to depend on AP-2. Knockdown of the two Arabidopsis AP2A genes or overexpression of a dominant-negative version of the medium AP-2 subunit, AP2M, impaired BRI1 endocytosis and enhanced the brassinosteroid signaling. Our data reveal that the CME machinery in Arabidopsis is evolutionarily conserved and that AP-2 functions in receptormediated endocytosis.

Adaptor protein complex 2-mediated endocytosis is crucial for male reproductive organ development in arabidopsis - Kim, Soo; Xu, Zheng; Song, Kyungyoung; Kim, Dae; Kang, Hyangju; Reichardt, Ilka; Sohn, Eun; Friml, Jirí; Juergens, Gerd; Hwang, Inhwan (Plant Cell)
Fertilization in flowering plants requires the temporal and spatial coordination of many developmental processes, including pollen production, anther dehiscence, ovule production, and pollen tube elongation. However, it remains elusive as to how this coordination occurs during reproduction. Here, we present evidence that endocytosis, involving heterotetrameric adaptor protein complex 2 (AP-2), plays a crucial role in fertilization. An Arabidopsis thaliana mutant ap2m displays multiple defects in pollen production and viability, as well as elongation of staminal filaments and pollen tubes, all of which are pivotal processes needed for fertilization. Of these abnormalities, the defects in elongation of staminal filaments and pollen tubes were partially rescued by exogenous auxin. Moreover, DR5rev:GFP (for green fluorescent protein) expression was greatly reduced in filaments and anthers in ap2m mutant plants. At the cellular level, ap2m mutants displayed defects in both endocytosis of N-(3-triethylammonium-propyl)-4- (4-diethylaminophenylhexatrienyl) pyridinium dibromide, a lypophilic dye used as an endocytosis marker, and polar localization of auxin-efflux carrier PIN FORMED2 (PIN2) in the stamen filaments. Moreover, these defects were phenocopied by treatment with Tyrphostin A23, an inhibitor of endocytosis. Based on these results, we propose that AP-2-dependent endocytosis plays a crucial role in coordinating the multiple developmental aspects of male reproductive organs by modulating cellular auxin level through the regulation of the amount and polarity of PINs.

Regulation of auxin homeostasis and gradients in Arabidopsis roots through the formation of the indole-3-acetic acid catabolite 2-oxindole-3-acetic acid - Pěnčík, Aleš; Simonovik, Biljana; Petersson, Sara; Henyková, Eva; Simon, Sibu; Greenham, Kathleen; Zhang, Yi; Kowalczyk, Mariusz; Estelle, Mark; Zažímalová, Eva; Novák, Ondřej; Sandberg, Göran; et al. (Plant Cell)
The native auxin, indole-3-acetic acid (IAA), is a major regulator of plant growth and development. Its nonuniform distribution between cells and tissues underlies the spatiotemporal coordination of many developmental events and responses to environmental stimuli. The regulation of auxin gradients and the formation of auxin maxima/minima most likely involve the regulation of both metabolic and transport processes. In this article, we have demonstrated that 2-oxindole-3-acetic acid (oxIAA) is a major primary IAA catabolite formed in Arabidopsis thaliana root tissues. OxIAA had little biological activity and was formed rapidly and irreversibly in response to increases in auxin levels. We further showed that there is cell type-specific regulation of oxIAA levels in the Arabidopsis root apex. We propose that oxIAA is an important element in the regulation of output from auxin gradients and, therefore, in the regulation of auxin homeostasis and response mechanisms.

A map of cell type‐specific auxin responses - Bargmann, Bastiaan; Vanneste, Steffen; Krouk, Gabriel; Nawy, Tal; Efroni, Idan; Shani, Eilon; Choe, Goh; Friml, Jirí; Bergmann, Dominique; Estelle, Mark; Birnbaum, Kenneth (Molecular Systems Biology)
In plants, changes in local auxin concentrations can trigger a range of developmental processes as distinct tissues respond differently to the same auxin stimulus. However, little is known about how auxin is interpreted by individual cell types. We performed a transcriptomic analysis of responses to auxin within four distinct tissues of the Arabidopsis thaliana root and demonstrate that different cell types show competence for discrete responses. The majority of auxin‐responsive genes displayed a spatial bias in their induction or repression. The novel data set was used to examine how auxin influences tissue‐specific transcriptional regulation of cell‐identity markers. Additionally, the data were used in combination with spatial expression maps of the root to plot a transcriptomic auxin‐response gradient across the apical and basal meristem. The readout revealed a strong correlation for thousands of genes between the relative response to auxin and expression along the longitudinal axis of the root. This data set and comparative analysis provide a transcriptome‐level spatial breakdown of the response to auxin within an organ where this hormone mediates many aspects of development.

Local auxin sources orient the apical basal axis in arabidopsis embryos - Robert, Hélène; Grones, Peter; Stepanova, Anna; Robles, Linda; Lokerse, Annemarie; Alonso, Jose; Weijers, Dolf; Friml, Jirí (Current Biology)
Establishment of the embryonic axis foreshadows the main body axis of adults both in plants and in animals, but underlying mechanisms are considered distinct. Plants utilize directional, cell-to-cell transport of the growth hormone auxin [1, 2] to generate an asymmetric auxin response that specifies the embryonic apical-basal axis [3-6]. The auxin flow directionality depends on the polarized subcellular localization of PIN-FORMED (PIN) auxin transporters [7, 8]. It remains unknown which mechanisms and spatial cues guide cell polarization and axis orientation in early embryos. Herein, we provide conceptually novel insights into the formation of embryonic axis in Arabidopsis by identifying a crucial role of localized tryptophan-dependent auxin biosynthesis [9-12]. Local auxin production at the base of young embryos and the accompanying PIN7-mediated auxin flow toward the proembryo are required for the apical auxin response maximum and the specification of apical embryonic structures. Later in embryogenesis, the precisely timed onset of localized apical auxin biosynthesis mediates PIN1 polarization, basal auxin response maximum, and specification of the root pole. Thus, the tight spatiotemporal control of distinct local auxin sources provides a necessary, non-cell-autonomous trigger for the coordinated cell polarization and subsequent apical-basal axis orientation during embryogenesis and, presumably, also for other polarization events during postembryonic plant life [13, 14].

Modeling framework for the establishment of the apical-basal embryonic axis in plants - Wabnik, Krzysztof T; Robert, Hélène; Smith, Richard; Friml, Jirí (Current Biology)
The apical-basal axis of the early plant embryo determines the body plan of the adult organism. To establish a polarized embryonic axis, plants evolved a unique mechanism that involves directional, cell-to-cell transport of the growth regulator auxin. Auxin transport relies on PIN auxin transporters [1], whose polar subcellular localization determines the flow directionality. PIN-mediated auxin transport mediates the spatial and temporal activity of the auxin response machinery [2-7] that contributes to embryo patterning processes, including establishment of the apical (shoot) and basal (root) embryo poles [8]. However, little is known of upstream mechanisms guiding the (re)polarization of auxin fluxes during embryogenesis [9]. Here, we developed a model of plant embryogenesis that correctly generates emergent cell polarities and auxin-mediated sequential initiation of apical-basal axis of plant embryo. The model relies on two precisely localized auxin sources and a feedback between auxin and the polar, subcellular PIN transporter localization. Simulations reproduced PIN polarity and auxin distribution, as well as previously unknown polarization events during early embryogenesis. The spectrum of validated model predictions suggests that our model corresponds to a minimal mechanistic framework for initiation and orientation of the apical-basal axis to guide both embryonic and postembryonic plant development.

ZIFL1.1 transporter modulates polar auxin transport by stabilizing membrane abundance of multiple PINs in Arabidopsis root tip - Remy, Estelle; Baster, Pawel; Friml, Jirí; Duque, Paula (Plant Signaling & Behavior)
Cell-to-cell directional flow of the phytohormone auxin is primarily established by polar localization of the PIN auxin transporters, a process tightly regulated at multiple levels by auxin itself. We recently reported that, in the context of strong auxin flows, activity of the vacuolar ZIFL1.1 transporter is required for fine-tuning of polar auxin transport rates in the Arabidopsis root. In particular, ZIFL1.1 function protects plasma-membrane stability of the PIN2 carrier in epidermal root tip cells under conditions normally triggering PIN2 degradation. Here, we show that ZIFL1.1 activity at the root tip also promotes PIN1 plasma-membrane abundance in central cylinder cells, thus supporting the notion that ZIFL1.1 acts as a general positive modulator of polar auxin transport in roots.